2018
DOI: 10.5603/gp.a2018.0081
|View full text |Cite
|
Sign up to set email alerts
|

Simple vaginal trachelectomy for early stage cervical cancer: A tertiary cancer center experience

Abstract: Objectives: Less radical fertility sparing procedures have been introduced to reduce morbidity and adverse obstetric outcome in cervical cancer. Our objective was to describe oncological and obstetric outcomes of women with early-stage cervical cancer who underwent a simple vaginal trachelectomy (SVT). Material and methods: From 01/2013 to 05/2017, 14 women underwent SVT preceded by laparoscopic pelvic lymph node dissection. Results: Patients' median age was 32 years and all of them were nulliparous. Histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this combined group, the authors found a 5-year progression-free survival of 97.9% and overall survival of 97.6%, with only one recurrence and death (2%) occurring in a patient who underwent simple trachelectomy [ 21 ]. These findings are similar to a smaller retrospective review of 14 women who underwent simple vaginal trachelectomy with no recurrences [ 22 ]. Raju et al in 2011 reviewed data from 66 women who either underwent simple vs. radical vaginal trachelectomy [ 23 ].…”
Section: Options For Fertility-sparing Treatmentsupporting
confidence: 88%
“…In this combined group, the authors found a 5-year progression-free survival of 97.9% and overall survival of 97.6%, with only one recurrence and death (2%) occurring in a patient who underwent simple trachelectomy [ 21 ]. These findings are similar to a smaller retrospective review of 14 women who underwent simple vaginal trachelectomy with no recurrences [ 22 ]. Raju et al in 2011 reviewed data from 66 women who either underwent simple vs. radical vaginal trachelectomy [ 23 ].…”
Section: Options For Fertility-sparing Treatmentsupporting
confidence: 88%
“…Conization procedures have been described as cold knife cone, large loop excision of the transformation zone, and laser conization [8,13,33,34,47]. Alternatively, SVT involves ligation of the bilateral descending branches of the uterine arteries, followed by amputation of the lower portion of the cervix with a 1-cm gross margin and at times including a 1-cm proximal vaginal resection [11,44,47]. Fertility is able to be preserved in 81% to 100% of the patients with this approach [34].…”
Section: Methodsmentioning
confidence: 99%
“…The literature search yielded a total of 937 studies, of which 355 duplicates were removed; 582 titles were screened against our inclusion criteria, and 452 abstracts were fully assessed. Of those abstracts, 130 full texts were scrutinised, and 51 failed to meet the inclusion criteria, leaving 79 studies for inclusion in our analysis 25,38–115 . Additionally, the literature search yielded several systematic reviews, which were manually assessed, and we identified a further 25 studies not captured by the initial literature search 26,116–139 …”
Section: Resultsmentioning
confidence: 99%